Non-Gaussian fatigue analysis of packaged fruit under random vibration using an improved CEEMDAN hybrid Gaussian decomposition approach - Song-Ping Yang; Jun-Ye He; He-Mu Yu; Tong Ji; Zhi-Wei Wang (Postharvest Biology and Technology, 2026)

4-Pentenoic acid exhibits broad-spectrum antibacterial activity against foodborne pathogens by disrupting bacterial membrane integrity and inhibiting efflux pump systems - Jiaming Mu; Jie Li; Fushuang Duan; Rui Wen; Xuepeng Cai; Qingling Meng; Jun Qiao; Zhongmei Ma (International Journal of Food Microbiology, 2026)

Sequential doping strategy for all-biomass derived N/P co-doped biochar: Unraveling the divergent capture mechanisms in antibiotic removal - Chengyu Li; Qihang Wang; Kunxiang Zhang; Hong He; Lvxin Peng; Jun Mu (Bioresource Technology, 2026)

Optimization of well patterns for heat recovery in sedimentary geothermal systems: A hybrid GRA-COBRA approach - Jun Xie; Shuxing Mu; Yuxuan Liu (Geothermics, 2026)

Critical overview of Peracetic acid-based advanced oxidation processes: Evolution, fundamentals and water treatment applications - Yongbo Yu; Jiaxin Yu; Haochen Zhang; Yongchao Mu; Yanjun Xin; Bin Zhang; Jun Ma (Chemical Engineering Journal, 2026)

Diurnal variations in air temperatures along cold region tunnels: Field observation and analytical solution - Lijie Zhang; Yanhu Mu; Xiaoming Zhu; Zhaohui Yang; Jun Hu; Chengcheng Du; Xiangbing Kong (Cold Regions Science and Technology, 2026)

WDS-Modality: A Physics-Informed Multi-Modal Agent Framework for Resilient Water Distribution System Assessment Using Large Language Models without Fine-tuning - Tianwei Mu; Yue Wang; Manhong Huang; Mingzhe Yuan; Dan Xue; Wenhong Wang; Hui Yang; Jun Li; Bo Zhou (Water Research, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Calvatia lilacina spores extract and engineered E. coli Nissle 1917 remodel the diabetic wound microenvironment through combined treatment - Tangtang He; Yan Li; Tiantian Dong; Tianjie Yuan; Wen Min; Ruoyu Mu; Jun Chen (Food Research International, 2026)

Origin of the heterogeneous enrichment of critical elements (Zr(Hf)-Nb(Ta)-Ga-REY) at the base of late permian tuffs, southwestern China - Tianyang Yang; Yulin Shen; Jian Shen; Lu Lu; Jun Jin; Xiwei Mu; Qinggen Bai; Aoyang Yang (International Geology Review, 2026)

A synergistic antifungal buccal composite integrating Aureobasidin A and alkaline modulation for localized treatment of oral candidiasis - Jiaxin Yi; Li Xie; Xueping Shui; Xinzhi Tan; Yandong Mu; Wei Fei; Li Xiao; Weidong Tian; Jun Guo (Chemical Engineering Journal, 2026)

A Systematic Survey and Geoconservation Strategy for Geoheritage Resources in the Guang’an Region, Southwest China - Sibao Zhu; Hong-Xu Mu; Zizheng Wang; Qingwei Song; Minghui Li; Qing Zhou; Jun Liu; Bangguo Zhou; Canhai Jin (Geoheritage, 2026)

Hydrodynamic characteristics of a partitioned recirculating aquaculture pond - Yuxin Liu; Jun Zhang; Shouqi Cao; Di Mu; Xingguo Liu; Bin Wang; Qian Yang; Yusheng Sun (Aquacultural Engineering, 2026)

Viability-based assessment of antibiotic resistance in Vibrio scophthalmi using propidium monoazide-qPCR - Hwa-Seong Son; Kun-Woo Yun; Min-Jun Seong; Sang-Min Lee; Mu-Chan Kim (Marine Environmental Research, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

Cooking water quality shapes the flavor, texture, and pasting properties of foxtail Millet: Associations with key water ions - Yiru Zhang; Pengyu Tian; Canran Zhang; Tingting Mu; Jun Zhang; Xiaodong Liu; Zhilong Meng (Journal of Cereal Science, 2026)

Laser-processed biomimetic hydrogel patches with tunable bio-adhesion, muscle tissue regeneration, and synergistic antibacterial activity - Luxing Wei; Jun Huang; Yingwen Mu; Liuguang Song; Yi Yu; Yuquan Wang; Gexing Peng; Ningji Gong; Jian Shen (Chemical Engineering Journal, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Axial compressive behavior of seawater sea-sand concrete filled double-skin aluminum tubular columns: A fundamental study for marine structures - Yan-jun Chang; Mu-yang Li; Yi-jie Zong; Li-li Jin (Ocean Engineering, 2026)

Sulfur vacancy-rich MoS2 nanoflowers as electron shuttles boost Fe(VI) activation for efficient micropollutant degradation - Lian Wu; Xin Zhou; Zi-Yi Han; Hui-Zhi Mu; Lu Wang; Yu-Lei Liu; Jun Ma (Journal of Hazardous Materials, 2026)

Intraguild predation risks revealed by functional responses: laboratory evaluation of three spider species preying on the generalist predatory Arma custos (Hemiptera: Pentatomidae) - Yin-Lin Mu; Jun-Yi Gao; Lin Yang; Mao-Xian Wang; Xiang-Sheng Chen (Phytoparasitica, 2026)

Spatiotemporal activity patterns of urban residents and nonlinear built-environment associations: Evidence from Shanghai using GPS traces and time-use diaries - Jing Guo; De Wang; Longxu Yan; Jing Xia; Lingting Mu; Yinong Liu; Jun Liu; Yuan Li (Applied Geography, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

A study on intramuscular fat deposition and flavor characteristics in different cuts of beef tongue - Shasha Li; Depeng Sun; Jingxi Nan; Yajie Li; Jun Zheng; Tingyu Li; Baide Mu; Guanhao Li; Chunxiang Piao (International Journal of Gastronomy and Food Science, 2026)

K isotope behavior in topsoil from the southeastern margin of the Tibetan Plateau - Yanan Cheng; Jun Mu; Peizheng He; Cheng Cao; Shichao An; Can Zhang; Xiaoping Feng; Cheng Zhao; Xiao-Ming Liu (Geochimica et Cosmochimica Acta, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Effects of forest type and elevation on plant and microbial residue carbon concentrations on Kunyu Mountain, China - Wei Zhu; Shiguo Gu; Jinyuan Wang; Tingting Mu; Yanyan Ni; Jun Gao; Mai-He Li (Journal of Soils and Sediments, 2026)

A combined biochar and biomineralization approach for enhanced soil Pb immobilization under accelerated aging - Huicong Hu; Zhengtao Shen; Chao-Sheng Tang; Wen Mu; Mengtao Wang; Sensen Li; Xiaohua Pan; Huan Liu; Bao-Jun Wang (Journal of Environmental Sciences, 2026)

Artificial sweetener acesulfame induces oxidative stress, neurotoxicity, and glycolipid metabolic disruption in zebrafish (Danio rerio) - Xue Liu; Qian Wang; Huijuan Lv; BaoYan Mu; Yali Zhou; Xianxu Li; Min Ding; Nan Jiang; Jun Wang (Environmental Pollution, 2026)

Sequential release of photodynamic hybrid HOFs and CeO₂ via a bilayer dynamic SIS hydrogel for periodontitis therapy - Shiqing Ma; Yujia Xiao; Yang Yu; Xiaotong Liu; Jiayin Deng; Yilin Yang; Shiyu Yao; Beibei Ma; Yo Shibata; Jun Zhou; Bo Zhao; Yuzhu Mu (Chemical Engineering Journal, 2026)

Identification of conserved vaccine targets in Mycoplasma bovis through integrated pan-genome and reverse vaccinology approaches with in vivo immunogenicity and safety evaluation - Jiaming Mu; Zhongmei Ma; Jie Li; Xuepeng Cai; Qingling Meng; Jun Qiao (The Veterinary Journal, 2026)

Species-specific eDNA monitoring and multivariate analysis for early warning of marine harmful organisms in a semi-enclosed Coastal Bay - Hwa-Seong Son; Kun-Woo Yun; Min-Jun Seong; Su Min Kim; Seung-Min Lee; Mu-Chan Kim (Regional Studies in Marine Science, 2026)

Deciphering the environmental fate of halogenated organic compounds in cold seep sediments: Insights from non-targeted analysis and metagenomics across vertical redox gradients - Hao Yu; Xiaoyan Zhang; Yanpeng Liang; Qinglin Mu; Xiaolei Shi; Zhaochao Deng; Jiawang Chen; Jun Cao; Yinan Deng; Zhiqiang Han; Haixin Chen; Chunfang Zhang (Journal of Hazardous Materials, 2026)

Integrative bulk and single-cell transcriptomic analyses reveal nucleus pulposus cell fibrosis as a therapeutic target in intervertebral disc degeneration and identify quercetin as a potential antifibrotic agent - Peilin He; Jun Tao; Guo Li; Ye Mu; Rong Hu; Junming Chen; Wenqi Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Simultaneous remediation of heavy metals in mining soil using nZVI-supported attapulgite - Jun Ren; Caili Tong; Hanru Ren; Ming Gao; Gui Ma; Yunmeng Li; Rui Zhu; Xuri Mu; Chun Yang; Ling Tao (Environmental Geochemistry and Health, 2026)

Design of robot navigation system under spatial constraints in shiitake mushroom fruiting room - Hualu Song; Kangkang Qi; Wenjie Feng; Yuanjie Mu; Jun Li; Xiangyu Lv; Zhichao Liang; Fengyun Wang (Computers and Electronics in Agriculture, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

A weakly supervised approach for large-scale agricultural parcel extraction from VHR imagery via foundation models and adaptive noise correction - Wenpeng Zhao; Shanchuan Guo; Xueliang Zhang; Pengfei Tang; Xiaoquan Pan; Haowei Mu; Chenghan Yang; Zilong Xia; Zheng Wang; Jun Du; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

Insights into co-occurrence characteristics and interplay of microbial communities and environmental pollutants on biofilm-colonized microplastics in mangrove ecosystems - Tao Yang; Xudong Ye; Xi Deng; Jun Mu; Min Liu; Jianhui Lin; Yuangao Qu; Yingxu Zeng (Water Research, 2026)

Mycotoxin deoxynivalenol drives antibiotic resistance evolution in Bacillus cereus via cell wall remodeling, compromising clinically critical antibiotics - Fengru Deng; Linyu Ke; Mi Huang; Meichan Chen; Zhongsong Chen; Peiqiang Mu; Mengzhuo Shi; Jun Wu; Yiqun Deng (Journal of Hazardous Materials, 2026)

Microbial succession–potential influence mechanism on flavor modulation in spontaneously fermented Moringa oleifera leaves: An integrative multi-omics approach - Yuhan Liu; Yuwei Guo; Hongyu Mu; Muhammad Aaqil; Feng Zhang; Jingchuan Zheng; Jun Sheng; Yang Tian; Cunchao Zhao (Food Research International, 2026)

Medium and long-chain triacylglycerol modified enhances alpha-linolenic acid bioavailability of silkworm pupa oil: A comparative study with plant-based oils - Funi Chen; Dongxu Xing; Siyuan Wang; Lixia Mu; Saiyi Zhong; Jun Liu; Zhiming Wang; Yang Xiao; Sentai Liao; Weifei Wang; Yuxiao Zou (Food Chemistry, 2026)

Improving hydro-mechanical response of heavy metal contaminated soil to rainfall events through combination of biochar and microbial induced carbonate precipitation (BM) treatment - Huicong Hu; Chao-Sheng Tang; Zhengtao Shen; Xiaohua Pan; Kai Gu; Mengtao Wang; Wen Mu; Bao-Jun Wang; Huan Liu; Zhihan Ji; Weiqiang Li (Engineering Geology, 2026)

Research progress on exogenous substances and their mechanisms of action in alleviating low-temperature stress in plants - Jiayi Chen; Qian Zhou; Qiong Wu; Jun Yang; Bihui Huang; Wenli Mu; Qinshuang Mei; Heping Zhao; Haifang Hu; Fenglan Liu; Jing Guo; Huixin Zhao (Planta, 2026)

Biota occurrence, accumulation, disposition and toxic effect of chlorinated paraffins - Huiming Zhang; Yutong Yang; Mu Zhang; Xue Li; Yan Zhang; Shufen Han; Rong Chen; Jun Yang; Jianyun Zhang (Environmental Geochemistry and Health, 2026)

Immobilization mechanism of Ca(H2PO4)2-modified attapulgite on multiple heavy metals in mining soils: Speciation changes, risk assessment and ecotoxicity - Jun Ren; Rui Zhu; Hanru Ren; Ling Tao; Xuri Mu (Science of The Total Environment, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

AE-TD3 with adaptive expert guidance: towards responsive deep reinforcement learning for building HVAC control systems - Zeqing Wu; Yunfei Mu; Xiaolong Jin; Yanze Xu; Hongjie Jia; Jun Zhao (Energy and Buildings, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Long Non-Coding RNA PVT1 Inhibits Apoptosis Through the miR-30d-5p/CaMKIIδ Axis in Hypoxic–Ischemic Brain Injury - Fengyan Zhao; Junyan Liu; Zihong Xiong; Lingyi Huang; Yuanyuan Zhao; Shiping Li; Junjie Ying; Qian Liu; Shaopu Wang; Xiaojuan Su; Jun Tang; Yi Qu; et al. (Molecular Neurobiology, 2026)

Excavation-induced soil disturbance assessment of soft clay behind the diaphragm wall - Yan-Guo Zhou; Mu-Zhi Li; Yu Tian; Jun-Neng Ye; Wei-An Lin; Yun-Min Chen (Tunnelling and Underground Space Technology, 2025)

Synergistic construction of an annual 2 m mangrove species dataset from 2016 to 2023 using structural features and hybrid stacked deep learning models—Beibu Gulf, Guangxi, China - Jun Sun; Weiguo Jiang; Ziyan Ling; Bolin Fu; Ze Zhang; Zhijie Xiao; Xingling Mu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Does ecological restoration really improve ecosystem stability? ——An empirical test based on the Minjiang River Basin of China - Hanchu Du; Jinman Wang; Jun Wang; Biao Liu; Jiayin Mu; Xiao Zhang (Ecological Engineering, 2025)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Morphology of root systems and tensile properties of individual roots across various soil types and layer thicknesses induced by bedrock weathering - Bin-bin Guo; Qing-yi Mu; Yan-jun Shen; Anthony Kwan Leung; Jian-bing Peng (CATENA, 2025)

Impact of Foliar Application of Zinc Sulphate with Nitrogen Fertilizer on Morphological Responses and Yield Improvement of Winter Wheat (Triticum aestivum L.) - Riaz Ahmed; Junyi Mu; Jun Xing; Mehr Un Nisa; Yulai Zhang; Pengcheng Ding; Linghong Li; Ying You; Aixia Ren; Zhiqiang Gao; Min Sun (International Journal of Plant Production, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Preparation, characterization, and stability analysis of monascus red pigments water-in-oil emulsion - Shuang Wang; Weijia Yuan; Jun Liu; Jianfei Mu; Yongguang Guan; Yangchao Luo; Ying Liang (Food Chemistry, 2025)

Effect of mixing and compaction methods on the physical properties, strength and microstructure of phase change material-modified soils under freeze-thaw process - Jun Bi; Yuxuan Pan; Wenxuan Mu; Mingyi Zhang; Guiyu Zhao; Haoxin Chen; Pengfei Liu (Cold Regions Science and Technology, 2025)

Remediation mechanism of KH2PO4 modified attapulgite on mining soil contaminated by heavy metals - Jun Ren; Xuri Mu; Hanru Ren; Ling Tao; Rui Zhu (Journal of Environmental Chemical Engineering, 2025)

An abrupt change in source materials for Chinese loess deposits at the Pliocene-Pleistocene boundary: Insights from K isotopes and modeling - Jun Mu; Jiawei Da; Hu Yang; Junfeng Ji; Lianwen Liu; Weiqiang Li (Earth and Planetary Science Letters, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Enhanced biodegradation of crude oil by phosphate-solubilizing bacteria Bacillus subtilis PSB-1: Overcoming soluble phosphorus deficiency - Xudong Wang; Zhuorong Du; Zhenzhen Li; Mei Liu; Jun Mu; Lijuan Feng; Zhi Chen; Qingguo Chen (Journal of Environmental Management, 2025)

Mixotrophy in Pyrophacus horologium (thecate dinoflagellate): predation on toxic and harmful dinoflagellates and molecular phylogenetics - Min-jun Seong; Kun-woo Yun; Hwa-seong Son; Seung-min Lee; Mu-chan Kim (Marine Biology, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Contaminant transport in a municipal solid waste landfill: On-site assessment and numerical modelling of vertical barrier wall effectiveness - Lin Mu; Qiao Wang; Fusheng Zha; Jun Wang; Rumin Xu; Miao Piao (Waste Management, 2025)

The driving effect of marine industries on marine pollution: Empirical evidence from coastal China - Cong Yu; Zifei Liu; Xianghui Kong; Runsheng Pei; Wanchanok Umprasoet; Yongtong Mu; Jun Xu (Journal of Cleaner Production, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Improving smartphone precise positioning based on a new weighting method - Liwenle Liu; Jun Huang; Xiaopeng Gong; Jinming Mu; Lei Xia; Shengfeng Gu; Yidong Lou (GPS Solutions, 2025)

A robust CMCNa-PAM salt-inhibiting double-network hydrogel for efficient solar interfacial evaporation - Junzhe Huang; Jianhua Zhou; Yang Long; Xiaojiang Mu; Zhixiang Zhang; Yanqing Zhu; Gang Xu; Jing Liu; Jun-Liang Chen; Lei Miao (Journal of Environmental Chemical Engineering, 2025)

A Review on Development, Challenges, and Future Perspectives of Ensemble Forecast - Jing Chen; Yuejian Zhu; Wansuo Duan; Xiefei Zhi; Jinzhong Min; Xiaoli Li; Guo Deng; Huiling Yuan; Jie Feng; Jun Du; Qiaoping Li; Jiandong Gong; et al. (Journal of Meteorological Research, 2025)

A model based on spectral invariant theory for correcting topographic effects on vegetation canopy reflectance - Weihua Li; Guangjian Yan; Jun Geng; Yuhan Guo; Tian Xie; Xihan Mu; Donghui Xie; Jean-Louis Roujean; Guoqing Zhou; Jean-Philippe Gastellu-Etchegorry (Remote Sensing of Environment, 2025)

Sedimentary heavy metal interactions with phytoplankton and zooplankton across the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Environmental Management, 2025)

A new control strategy of sulfate-reducing microorganisms and corrosion rate from a high-temperature oil reservoir by nitrate/nitrite coupling with nitrate-reducing bacteria - Lei Zhou; Jie Gao; Yu-Xuan Li; Jun Wu; Biao Wang; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

The K isotopic signatures of coals: A reconnaissance study - Zhihan Ji; Jun Mu; Suping Yao; Weiqiang Li (International Journal of Coal Geology, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Do emerging alternatives pose similar soil ecological risks as traditional plasticizers? A multi-faceted analysis using earthworms as a case study - Huijuan Lv; Baoyan Mu; Haixia Xu; Xianxu Li; Xiangfeng Yao; Qian Wang; Huiyan Yang; Jia Ding; Jun Wang (Journal of Hazardous Materials, 2025)

Facilitating Fe2+ regeneration via biochar to activate peroxydisulfate for pollutants removal: Degradation mechanism and quantitative structure-activity relationship model - Bowen Yang; Zhengyi Fan; Dongqi Mu; Qiang Ma; Dunqiu Wang; Jian Wang; Longhui Zheng; Zhiwen Cheng; Jun Zhang (Journal of Environmental Chemical Engineering, 2025)

Probiotic potential of lactic acid bacteria with antioxidant properties in modulating health: Mechanisms, applications, and future directions - Yuan Gao; Qimeng Liang; Junqi Sun; Xiaomeng Wu; Yinglong Song; Yunpeng Xu; Hui Nie; Jun Huang; Guangqing Mu (Food Bioscience, 2025)

Hypogene sulfide precipitation during phyllic alteration: insights from copper isotopic evolution of the Dexing porphyry Cu–Mo–Au deposit, South China - Jia-Feng He; Guo-Guang Wang; Matthew J. Brzozowski; Pei Ni; Xiang-Long Luo; Jun Mu; Weiqiang Li (Mineralium Deposita, 2025)

A novel and flexible way to derive water quality criteria for copper - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Science of The Total Environment, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Combination mechanism and dimethyl ether removal performance of organic-bound water in kitchen waste - Jipeng Sun; Wei Zhu; Jun Zhong; Biao Mu; Xin Wang; Xinyi Wang; Yucheng Xu; Jun Cao; Naixi Lin (Waste Management, 2025)

A compliant helical structure to amplify inertia for nonlinear vibration absorption - Jun-Jie Huang; Mu-Qing Niu; Yimin Fan; Li-Qun Chen (Engineering Structures, 2025)

An isolate of human blood-associated partitivirus naturally infects the phytopathogenic fungus Bipolaris maydis - Kun Zhang; Ge Mu; Weilan Wu; Peng Wang; Jun Shang; Changquan Li; Qingchao Deng; Shouguo Fang; Haoran Wang; Songbai Zhang (Archives of Virology, 2025)

Application of acid-activated attapulgite clay on effective immobilization of Cd in paddy soils - Ling Tao; Zhijie Yang; Hanru Ren; Yuchen Jiang; Yunmeng Li; Xuri Mu; Jun Ren (Environmental Science and Pollution Research, 2024)

Regionally adapted conservation tillage reduces the risk of crop yield losses: A global meta-analysis - Jun Sun; Wenquan Niu; Yadan Du; Li Ma; Siying Huang; Fei Mu; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

Role and mechanism of the outer membrane porin LamB in T-2 mycotoxin-mediated extensive drug resistance in Escherichia coli - Fengru Deng; Li Zhao; Ping Wei; Enhua Mai; Meichan Chen; Huixin Yang; Peiqiang Mu; Jun Wu; Jikai Wen; Yiqun Deng (Journal of Hazardous Materials, 2024)

Microplastic pollution in tropical coral reef ecosystems from the coastal South China Sea and their impacts on corals in situ - Weijie Bian; Yingxu Zeng; Yurui Li; Guangshui Na; Jun Mu; Shuguo Lv; Min Liu (Journal of Hazardous Materials, 2024)

Comparison of primary and secondary metabolites and antioxidant activities by solid-state fermentation of Apios americana Medikus with different fungi - Hee Yul Lee; Hyo Seon Kim; Min Ju Kim; Young Hye Seo; Du Yong Cho; Ji Ho Lee; Ga Young Lee; Jong Bin Jeong; Mu Yeun Jang; Jin Hwan Lee; Jun Lee; Kye Man Cho (Food Chemistry, 2024)

A sprayable and rapidly cross-linked hydrogel membrane for fruit preservation - Luxing Wei; Xiaoyong Qiu; Yingwen Mu; Limin Zhang; Jian Shen; Shunji Yang; Xiangyu Zhou; Yungang Gai; Shuyuan Wang; Jun Huang (Food Packaging and Shelf Life, 2024)

Derivation of marine water quality criteria for copper based on artificial neural network model - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Environmental Pollution, 2024)

Efficient phosphate recovery and treatment of high-phosphorus wastewater using sodium alginate-immobilized microspheres based on aluminum-rich water treatment plant sludge - Guorui Li; Wei Zhu; Jun Zhong; Jipeng Sun; Yichao Wang; Biao Mu; Xin Wang; Yucheng Xu (Environmental Pollution, 2024)

Ecotoxicological risk of co-exposure to fosthiazate and microplastics on earthworms (Eisenia fetida): Integrating biochemical and transcriptomic analyses - Chonglin Xu; Xiangfeng Yao; Weizheng Kong; Baoyan Mu; Guilan Duan; Jun Wang; Yuxin Xu; Xianxu Li (Environmental Pollution, 2024)

Exploring of laccase-like nanozyme and membrane filters for efficient removal of tetracycline hydrochloride - Yun Wang; Dan Wang; Qixuan Mu; Yanke Zhai; Jun Hai; Yibing Ji; Ruijun Li (Chemical Engineering Journal, 2024)

An extension to ensemble forecast of conditional nonlinear optimal perturbation considering nonlinear interaction between initial and model parametric uncertainties - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Xing-Rong Chen; Bo Qin; Guo-Kun Dai (Atmospheric Research, 2024)

Comparative analysis of complete chloroplast genomes of 14 Asteraceae species - Riwa Mahai; Shasha Sheng; Xiaoyun Wang; Jun Yuan; Zejing Mu (Molecular Biology Reports, 2024)

NHX5/NHX6/SPY22 complex regulates BRI1 and brassinosteroid signaling in Arabidopsis - Jun Shang; Guoxiu Mu; Yuting Qi; Xiao Zhang; Wei Shen; Yujie Xie; Mingrui Ge; Yu He; Feng Qiao; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

Enhanced eDNA monitoring for detection of viable harmful algal bloom species using propidium monoazide - Kun-woo Yun; Hwa-seong Son; Min-jun Seong; Seung-min Lee; Mu-chan Kim (Harmful Algae, 2024)

Western Mongolian Plateau exhibits increasing Holocene temperature - Chong Huang; Xiaozhong Huang; Jinbao Li; Ling Wang; Lan Jiang; Lixiong Xiang; Jun Zhang; Yu Hu; Xiaoyan Mu; Min Zheng; Xiuxiu Ren; Tao Wang; et al. (Global and Planetary Change, 2024)

Sub-chronically exposing zebrafish to environmental levels of methomyl induces dysbiosis and dysfunction of the gut microbiota - Mingxiao Li; Xi Chen; Chao Song; Limin Fan; Liping Qiu; Dandan Li; Huimin Xu; Shunlong Meng; Xiyan Mu; Bin Xia; Jun Ling (Environmental Research, 2024)

Application of Fluorescent Composite Materials as a Sustained Release System in Treatment of Polycystic Ovary Syndrome - Lin Wang; Liangshan Mu; Yao Ye; Jun Xu; Xutong Zou (Journal of Fluorescence, 2024)

A vapor phase side stream intensified extractive distillation process for separation of azeotropic mixture 2, 2, 2-trifluoroethanol and water - Dongmei Xu; Jinxing Mu; Hailin Sun; Sixuan Tao; Jun Gao; Zhishan Zhang; Lianzheng Zhang; Yixin Ma; Yinglong Wang (Process Safety and Environmental Protection, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Bio-refinery of palm kernel expeller waste into attached microalgal biodiesel, the life cycle analysis of waste biomass-to-energy - Hemamalini Rawindran; Kuan Shiong Khoo; Ratchaprapa Raksasat; Chin Seng Liew; Wai Hong Leong; M. Devendran; Balasubramani Ravindran; Woei-Yenn Tong; Jin Chung Sin; Sze Mun Lam; Mu. Naushad; Jun Wei Lim (Process Safety and Environmental Protection, 2024)

Advancements and prospects in the utilization of metal ions and polymers for enhancing aerobic granulation during industrial effluent treatment and resource recovery - Ahmad Hussaini Jagaba; Dahiru U. Lawal; Ismail Abdulazeez; Ibrahim Mohammed Lawal; Nuhu Dalhat Mu'azu; Abdullahi Haruna Birniwa; Abdullahi Kilaco Usman; Haithm Salah Hagar; Nura Shehu Aliyu Yaro; Azmatullah Noor; Kunmi Joshua Abioye; Jun Wei Lim; et al. (Journal of Water Process Engineering, 2024)

Implications of ocean warming and acidification on heavy metals in surface seawater of the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Effect and application of spray drying and freeze drying on characterization of walnut oil microcapsules - Mingming Wang; Hongyu Mu; Lei Peng; Chunlei Tan; Yinyan Chen; Jun Sheng; Yang Tian; Cunchao Zhao (Journal of Food Engineering, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Nickel augmented biochar for sustaining produced water treatment to decarbonize oil and gas industrial waste using anaerobic-aerobic granular cylindrical periodic discontinuous batch reactors - Ahmad Hussaini Jagaba; Dahiru U. Lawal; Mohamed A. Yassin; Ismail Abdulazeez; Nuhu Dalhat Mu'azu; Abdullahi Kilaco Usman; Jun Wei Lim; Isam H. Aljundi (Environmental Research, 2024)

A review on the application of biochar as an innovative and sustainable biocarrier material in moving bed biofilm reactors for dye removal from environmental matrices - Ahmad Hussaini Jagaba; Ismail Abdulazeez; Dahiru U. Lawal; Augustine Chioma Affam; Nuhu Dalhat Mu’azu; Usman Bala Soja; Abdullahi Kilaco Usman; Azmatullah Noor; Jun Wei Lim; Isam H. Aljundi (Environmental Geochemistry and Health, 2024)

Anthropogenic forest degradation and its impact on soil erosion in the mountainous region of northern China - Xiuxiu Ren; Chong Huang; Zezhou Zhu; Ling Wang; Ning Wang; Xiaoyan Mu; Derui Luo; Jun Zhang; Lixiong Xiang; Xiaozhong Huang (CATENA, 2024)

Missing microbes in infants and children in the COVID-19 pandemic: a study of 1,126 participants in Beijing, China - Jiejing Wang; Yuejuan Li; Yu Mu; Kefei Huang; Danyi Li; Canhui Lan; Yutao Cui; Jun Wang (Science China Life Sciences, 2024)

Marinobacter sediminicola sp. nov. and Marinobacter xiaoshiensis sp. nov., Isolated from Coastal Sediment - Jing An; Run-Yuan Mao; Shu-Xin Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Current Microbiology, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Effect of dulcitol on growth performance, antioxidant activity, immune function, and intestinal microflora of growing-finishing pigs - Zhengqun Liu; Shiyue Liang; Diankui Wang; Zi Zheng; Ning Li; Chunhua Zhang; Jun Yan; Renmin Liu; Pei He; Qianjun Li; Shuqin Mu (Livestock Science, 2024)

Enhanced electroreduction of low-concentration nitrate using a Cu-Pd bimetallic cathode system: Performance evaluation, mechanism analysis, and potential applications - Mu Yuan; Jun Sun; Yongli Wu; Min Zheng; Chenhao Sheng; Chao Wu; Qinian Wang (Journal of Environmental Chemical Engineering, 2024)

Developing intelligent Earth System Models: An AI framework for replacing sub-modules based on incremental learning and its application - Bin Mu; Zi-Jun Zhao; Shi-Jin Yuan; Bo Qin; Guo-Kun Dai; Guan-Bo Zhou (Atmospheric Research, 2024)

Volcanic Rock Landscapes and Natural Heritage Values of Mt. Chilbo, Democratic People’s Republic of Korea - Won-Sok Jon; To-Jun Ryang; Mu-Il Ri; Myong-Won Ri (Geoheritage, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Optimized tillage can enhance crop tolerance to extreme weather events: Evidence from field experiments and meta-analysis - Jun Sun; Wenquan Niu; Fei Mu; Ruoyu Li; Yadan Du; Li Ma; Qian Zhang; Guochun Li; Jinjin Zhu; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Maternal exposure to ZIF-8 derails placental function by inducing trophoblast pyroptosis through neutrophils activation in mice - Yu Jiang; Yanqing Geng; Rufei Gao; Zhuxiu Chen; Jun Chen; Xinyi Mu; Yan Zhang; Xin Yin; Xuemei Chen; Fangfang Li; Junlin He (Food and Chemical Toxicology, 2024)

A MYB transcription factor GhTT2 of Gossypium hirsutum regulates proanthocyanidin accumulation and improves osmotic tolerance in Arabidopsis - Jun Mei; Rongrong Mu; Qingqing Niu; Huimin Zhu; Ruoxi Chen; Xiaomiao Cai; Meng Miao; Dongliang Yu; Liping Ke; Yuqiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Equilibrium Mg and K isotope fractionation between carnallite and saturated brine: Calibrations and applications - Zhiguang Xia; Yongjie Lin; Dongdong Li; Lars Reuning; Zhongya Hu; Chuan Liu; Jun Mu; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Conversion of waste cork to N-doped porous carbons by urea-assisted hydrothermal method for enhanced VOC capture - Danwei He; Qihang Wang; Jun Mu (Waste Management, 2024)

First Pediastrum–temperature transfer function and its application to mid-to-late Holocene reconstruction in Central Asia - Lixiong Xiang; Xiaozhong Huang; Jiawu Zhang; Chong Huang; Antje Schwalb; Jifeng Zhang; Natalia Rudaya; Mingjie Sun; Xiaoyan Mu; Yuan Li; Derui Luo; Farqan Muhammad; et al. (Quaternary Science Reviews, 2024)

Physiological and transcriptomic response reveals new insight into manganese tolerance of Celosia argentea Linn. - Liyun Liang; Mu Ze; Jun Yang; Qian Xu; Cunmei Du; Xiaohong Hu; Ming Dong; Lijuan Zou; Tuo Qi (Journal of Hazardous Materials, 2024)

Embedding hydrogel electrodes into hydrogel Electrolyte: An 3D protecting strategy for stretchable High-Performance supercapacitor - Chuanling Mu; Jun Fang; Junlian Nie; Lu Fu; Wen Li (Chemical Engineering Journal, 2024)

Baking-inspired pore regulation strategy towards a hierarchically porous carbon for ultra-high efficiency cationic/anionic dyes adsorption - Qihang Wang; Jun Mu (Bioresource Technology, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Effects of electron acceptors and donors on anaerobic biodegradation of PAHs in marine sediments - Qingguo Chen; Zhenzhen Li; Yu Chen; Mei Liu; Qiao Yang; Baikang Zhu; Jun Mu; Lijuan Feng; Zhi Chen (Marine Pollution Bulletin, 2024)

Fosthiazate, a soil-applied nematicide, induces oxidative stress, neurotoxicity and transcriptome aberrations in earthworm (Eisenia fetida) - Can Wang; Xiangfeng Yao; Xianxu Li; Qian Wang; Nan Jiang; Xue Hu; Huijuan Lv; Baoyan Mu; Jun Wang (Journal of Hazardous Materials, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Potassium isotopic signatures of modern offshore detrital sediments from different climatic regimes and the implications - Jun Mu; Tianyu Chen; Qian Yu; Shichao An; Jianfang Chen; Xuefa Shi; Weiqiang Li (Science China Earth Sciences, 2024)

Hydrothermal carbonization of coking sludge: Formation mechanism and fuel characteristic of hydrochar - Jun Zhong; Wei Zhu; Jipeng Sun; Biao Mu; Xin Wang; Zongpu Xue; Jun Cao (Chemosphere, 2024)

Improved solid/liquid separation performance of hydrochar from sludge via hydrothermal carbonization - Jun Zhong; Wei Zhu; Biao Mu; Jipeng Sun; Xin Wang; Naixi Lin; Jun Cao (Journal of Environmental Management, 2023)

Somatic embryo induction and plantlet regeneration of Canna × generalis from immature zygotic embryo - Zu-yan Gan; Mu-lin Shu; Feng Yang; Guo-fang Wang; Wen-e Zhang; Xue-jun Pan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Fibrillarin promotes homologous recombination repair by facilitating the recruitment of recombinase RAD51 to DNA damage sites - Yanhua Mu; Jinhua Han; Mingjie Wu; Zongfang Li; Ke Du; Yameng Wei; Mengjie Wu; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2023)

Cerina litoralis gen. nov., sp. nov., a novel potential polysaccharide degrading bacterium of the family Flavobacteriaceae, isolated from marine sediment - Ya-Wei Wang; Xin-Hui Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Antonie van Leeuwenhoek, 2023)

Effect mechanism of iron conversion on adsorption performance of hydrochar derived from coking sludge - Jun Zhong; Wei Zhu; Xin Wang; Jipeng Sun; Biao Mu; Yucheng Xu; Guorui Li (Science of The Total Environment, 2023)

Effects of fermented bamboo powder on growth performance, apparent digestibility, carcass traits, and meat quality in growing-finishing pigs - Zi Zheng; Zhengqun Liu; Ning Li; Shuqin Mu; Shiyue Liang; Zhonghao Liu; Chunhua Zhang; Yuanming Li; Jun Yan; Qianjun Li (Livestock Science, 2023)

Review on fault-tolerant control of unmanned underwater vehicles - Fuqiang Liu; Zuxing Ma; Bingxian Mu; Chaoqun Duan; Rui Chen; Yi Qin; Huayan Pu; Jun Luo (Ocean Engineering, 2023)

Improving the yield and tetracycline adsorption performance of kitchen waste biochar through subcritical dimethyl ether pretreatment - Jipeng Sun; Wei Zhu; Jun Cao; Jun Zhong; Biao Mu; Xin Wang; Naixi Lin (Journal of Environmental Chemical Engineering, 2023)

Characterization of the differences in aroma-active compounds in strong-flavor Baijiu induced by bioaugmented Daqu using metabolomics and sensomics approaches - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Hanlan Tang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Improvement of catalytic activity of sorbose dehydrogenase for deoxynivalenol degradation by rational design - Danyang Li; Guoqiang Liang; Peiqiang Mu; Jinquan Lin; Jiarun Huang; Chongwen Guo; Yang Li; Ruqin Lin; Jun Jiang; Jun Wu; Yiqun Deng; Jikai Wen (Food Chemistry, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

Propidium Monoazide based selective iDNA monitoring method improves eDNA monitoring for harmful algal bloom Alexandrium species - Kun-Woo Yun; Hwa-Seong Son; Min-Jun Seong; Mu-Chan Kim (Frontiers in Marine Science, 2023)
eDNA, also known as environmental DNA, has garnered significant attention due to its potential applications in various fields such as biodiversity assessment, species distribution monitoring, ecological interaction analysis, and quantitative analysis. However, the presence of non-selective DNA signals in eDNA samples poses challenges in accurately detecting species, assessing biodiversity, and conducting quantitative analysis. To address these limitations, this study developed a novel method for selectively detecting iDNA from specific species in eDNA samples. The method involved the application of PMA treatment to Alexandrium spp. effectively preventing the detection of non-selective exDNA signals. Additionally, by optimizing the filter size used in the sampling process, the researchers were able to selectively collect and analyze iDNA from species of interest, particularly Alexandrium spp. Furthermore, the study successfully demonstrated the selective collection and analysis of iDNA from Alexandrium spp. cysts present in the sediment layer, further strengthening the findings. The results indicated that the combined use of PMA treatment and filter size optimization significantly enhanced the selective detection capability of iDNA. The successful selective detection of iDNA from eDNA in the sediment layer highlights the practical applicability of the developed method. This study holds promise for advancing eDNA monitoring technology by providing a selective iDNA detection method utilizing PMA. Moreover, these findings lay the foundation for effectively utilizing iDNA in environmental conservation, monitoring, and ecological research.

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

Degradation of tetracyclines via calcium peroxide activation by ultrasonic: Roles of reactive species, oxidation mechanism and toxicity evaluation - Zujun Xu; Shaofang Sun; Mingchang Gao; Ruibin Zheng; Haotian Mu; Liping Qiu; Jun Ma (Chemosphere, 2023)

Silibinin exerts neuroprotective effects against cerebral hypoxia/reoxygenation injury by activating the GAS6/Axl pathway - Weiping Li; Zhe Zhang; Jiawen Li; Jun Mu; Meng Sun; Xue Wu; Xiaochen Niu; Yang Yang; Huanle Yan; Xiaoling Xu; Chengxu Xue; Lu Qian; et al. (Toxicology, 2023)

Chromones from the whole plant of Hypericum elodeoides and their bioactivities - Yanbing Mu; Letian Cui; Ping Ying; Huiping Wen; Dujuan Zhan; Lingyi Kong; Jun Luo (Phytochemistry Letters, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Isolation and characterization of tumorigenic bacteria associated with crown gall disease of Prunus humilis Bunge in China - Rong Xiao; Xiao-Peng Mu; Jian-Cheng Zhang; Shuai Zhang; Chun-Fen Zhang; Shu Deng; Jun-Jie Du; Peng-Fei Wang (European Journal of Plant Pathology, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Characterization of Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov., revealing the potential nitrogen fixation capacity of the order Marinilabiliales - Wen-Xing Yu; Qi-Yun Liang; Zong-Jun Du; Da-Shuai Mu (Frontiers in Marine Science, 2023)
Biological nitrogen fixation plays a crucial role in the marine nitrogen cycle, impacting global marine productivity and related carbon fluxes. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences.These two strains were isolated from the coastal sediment at Xiaoshi Island in Weihai, China. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences. It was revealed that strains D04 T and AAT T contain a set of nif gene clusters responsible for nitrogen fixation. Cell are yellow-colored, Gram-stain-negative, facultatively anaerobic, and rod-shaped bacteria. The optimal growth conditions for strain D04 T were found to be at 33 °C, pH 7.0, and in 2% (w/v) NaCl, while strain AAT T prefers growth conditions at 33 °C, pH 6.5, and in 3% (w/v) NaCl. The highest similarity of strains D04 T and AAT T was to Saccharicrinis fermentans NBRC 15936 T , with a similarity of 94.1% and 94.8%, respectively. The 16S rRNA gene sequence similarity between the two strains was 96.6%. These novel strains were found to represent new taxa of the Marinilabiliaceae family, and we propose the names Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov. with type strains D04 T (MCCC 1H00493 T = KCTC 92026 T ) and AAT T (MCCC 1H00485 T = KCTC 92028 T ), respectively. In this study, nitrogen fixation genes were predicted for 53 strains from the whole order Marinilabiliales and it was found that nitrogen fixation gene clusters were present in 26 strains. These gene clusters were found in every family in the order, highlighting that the presence of nitrogen-fixing gene clusters in the order is common. Nitrogen-fixing bacteria in sediments play an important role in various biogeochemical cycles. Thus, understanding the oceanic nitrogen cycle can provide insights into the energy flow of marine systems.

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Dysfunction of NRG1/ErbB4 Signaling in the Hippocampus Might Mediate Long-term Memory Decline After Systemic Inflammation - Yu-zhu Gao; Xin-miao Wu; Zhi-qiang Zhou; Pan-miao Liu; Jian-jun Yang; Mu-huo Ji (Molecular Neurobiology, 2023)

Comparative genomics reveal distinct potential of Tamlana sp. S12 for algal polysaccharide degradation - Hai-Feng Xia; Xiao-Yu Jia; Yan-Xia Zhou; Zong-Jun Du; Da-Shuai Mu; Guan-Jun Chen (Frontiers in Marine Science, 2023)
Introduction Macroalgae contain various polysaccharides that serve as nutrient sources Introduction: Macroalgae contain various polysaccharides that serve as nutrient sources for marine bacteria. Carbohydrate-active enzymes (CAZymes) are the primary feature of marine bacteria that utilize these polysaccharides. In this study, we describe Tamlana sp. S12, a novel strain of marine flavobacteria that can degrade alginate and Laminaria japonica biomass, isolated from the intestines of the sea cucumber Apostichopus japonicas collected at Weihai coast. Methods We sequenced the entire genome of strain S12 and constructed a phylogenetic tree using the core genome sequences of related strains. We determined the enzymatic activity of strain S12 using the DNS method and measured its growth curve under different carbon sources using spectrophotometry. Results Strain S12 degraded dehydrated L. japonica fragments as the sole nutrient source within 48h. Strain S12 harbors a diverse array of CAZymes at multiple polysaccharide utilization loci (PUL). One PUL encoding lyases from PL6, 7, and 17 families may be used for the degradation of alginate. Additionally, strain S12 harbors PULs encoding carrageenan- and agar-targeting CAZymes. Comparative analysis with related flavobacteria from Algibacter , Maribacter , and Zobellia showed shared CAZymes among these strains, potentially derived from a common ancestor and stably maintained within strains. Genomic signatures, algal degradation ability, and CAZyme patterns suggest that strain S12 has the potential to degrade complex algal polysaccharides. Conclusion These results expand our knowledge of CAZymes and enrich our understanding of how marine Flavobacteriaceae adapt to marine algal polysaccharide environments. The availability of the genome of Tamlana sp. S12 will be beneficial for further analyses of marine Flavobacteriaceae.

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Life cycle assessment of stone buildings in the Taihang mountains of Hebei province: Evolution towards cleaner production and operation - Lingege Long; Qingxiang Li; Zhenkun Gan; Jun Mu; Mauro Overend; Dayu Zhang (Journal of Cleaner Production, 2023)

Influence of Lonicera japonica and Radix Puerariae crude extracts on the growth performance, antioxidant capacity, and immunological functions of finishing pigs - Zhonghao Liu; Jun Yan; Ning Li; Zi Zheng; Chunhua Zhang; Zhengqun Liu; Chunling Song; Shuqin Mu (Livestock Science, 2023)

Evaluation of the ventilation and pollutant exposure risk level inside 3D street canyon with void deck under different wind directions - Chung Hyok Sin; Kwang Song Jon; Gyong Ho Un; Yong Il Thae; Hun Kim; Jun Tokgo; Hyon Mu Ri (Environmental Science and Pollution Research, 2023)

Comprehensive analysis for the bioturbation effect of space mutation and biofortification on strong-flavor Daqu by high-throughput sequencing, volatile analysis and metabolomics - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Yi Dong; Chao Wang; Xiaojun Wang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Cinnamaldehyde affects lipid droplets metabolism after adipogenic differentiation of C2C12 cells - Yanrong Liu; Zhengqun Liu; Qiang Luo; Zhuwen Sun; Ning Li; Zi Zheng; Shuqin Mu; Xiaoqiao Zhou; Jun Yan; Chao Sun; Hongfu Zhang (Molecular Biology Reports, 2023)

Characteristics of microbiota, core sulfate-reducing taxa and corrosion rates in production water from five petroleum reservoirs in China - Lei Zhou; Jun Wu; Jia-Heng Ji; Jie Gao; Yi-Fan Liu; Biao Wang; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Science of The Total Environment, 2023)

Long-term environmental risks of the Baltic Sea's "memory effect" revealed by ocean modeling and observation of reprocessing-derived radiotracers - Mu Lin; Jun She; Jens Murawski; Xiaolin Hou; Jixin Qiao (Journal of Hazardous Materials, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Formation mechanisms and atmospheric implications of summertime nitrous acid (HONO) during clean, ozone pollution and double high-level PM2.5 and O3 pollution periods in Beijing - Huiying Xuan; Yaqi Zhao; Qingxin Ma; Tianzeng Chen; Jun Liu; Yonghong Wang; Chang Liu; Yafei Wang; Yongchun Liu; Yujing Mu; Hong He (Science of The Total Environment, 2023)

Single atom Co-anchored nitrogen‑doped graphene for peroxymonosulfate activation with high selectivity of singlet oxygen generation - Han-Qing Zhao; Jun-Sheng Song; Peili Lu; Yang Mu (Chemical Engineering Journal, 2023)

Predation capacity of Bradymonabacteria, a recently discovered group in the order Bradymonadales, isolated from marine sediments - Ya Gong; Xiu-Ya Ping; Chen-Hang Zeng; Shu-Xin Wang; Yi Zhou; Ming-Yi Wang; Da-Shuai Mu; Zong-Jun Du (Archives of Microbiology, 2022)

Benthic Sargassum composition and community characteristics in the intertidal zone of Hainan Island, China - Xiaoxiao Zou; Tian Meng; Dandan Yao; Zuo Chen; Jun Zhu; Dan Mu; Shixiang Bao (Marine Biology Research, 2022)

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

Hepatocyte steatosis inhibits hepatitis B virus secretion via induction of endoplasmic reticulum stress - Qichuang Liu; Maoyuan Mu; Huan Chen; Guoyuan Zhang; Yanqing Yang; Jun Chu; Ying Li; Fangwan Yang; Shide Lin (Molecular and Cellular Biochemistry, 2022)

Deoxynivalenol induces caspase-3/GSDME-dependent pyroptosis and inflammation in mouse liver and HepaRG cells - Xiaoxiao Mao; Jie Li; Xin Xie; Shuang Chen; Qiang Huang; Peiqiang Mu; Jun Jiang; Yiqun Deng (Archives of Toxicology, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Toxicokinetics and metabolism of deoxynivalenol in animals and humans - Yu Sun; Jun Jiang; Peiqiang Mu; Ruqin Lin; Jikai Wen; Yiqun Deng (Archives of Toxicology, 2022)

Robiginitalea marina sp. nov., isolated from coastal sediment - Xiao-Qi Xuan; Run-Yuan Mao; Wen-Xing Yu; Jing An; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

A 215-bp indel at intron I of BoFLC2 affects flowering time in Brassica oleracea var. capitata during vernalization - Qinfei Li; Ao Peng; Jiaqin Yang; Sidi Zheng; Zhangping Li; Yinhui Mu; Lei Chen; Jun Si; Xuesong Ren; Hongyuan Song (Theoretical and Applied Genetics, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Re-evaluation of the identities of Glossadelphus borneensis and its associated synonyms, G. attenuatus and G. nitidus - Zhao-Qin Yi; Si He; Jun-Jie Wang; Li-Qiang Mu; Yu Jia (Brittonia, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Psychroserpens luteolus sp. nov., isolated from Gelidium, reclassification of Ichthyenterobacterium magnum as Psychroserpens magnus comb. nov., Flavihalobacter algicola as Psychroserpens algicola comb. nov., Arcticiflavibacter luteus as Psychroserpens luteus comb. nov - Xiu-Ya Ping; Kai Wang; Jin-Yu Zhang; Shu-Xin Wang; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Cytotoxic benzopyranone and xanthone derivatives from a coral symbiotic fungus Cladosporium halotolerans GXIMD 02502 - Chao-Nan Wang; Hu-Mu Lu; Cheng-Hai Gao; Lang Guo; Zhen-Yu Zhan; Jun-Jian Wang; Yong-Hong Liu; Song-Tao Xiang; Jian Wang; Xiao-Wei Luo (Natural Product Research, 2021)

Maternal intake of caffeinated products and birth defects: a systematic review and meta-analysis of observational studies - Yan Yue; Wenxing Li; Jun Tang; Yan Zeng; Tao Xiong; Xia Qiu; Jing Shi; Hua Wang; Bin Xia; Lili Luo; Yi Qu; Dezhi Mu (Critical Reviews in Food Science and Nutrition, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Temporal stability analysis of soil moisture along a coniferous forest hillslope with subtropical monsoon climate in southwest China - Yu-shi Bai; Mu-xing Liu; Jun Yi; Hai-lin Zhang (Journal of Mountain Science, 2021)

Description of Lujinxingia vulgaris sp. nov., isolated from coastal sediment via prey-traps - Shuo Wang; Da-Shuai Mu; Guang-Yu Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2021)

Lessons Learned from the Tragedy during the 100 km Ultramarathon Race in Baiyin, Gansu Province on 22 May 2021 - Qinghong Zhang; Chan-Pang Ng; Kan Dai; Jun Xu; Jian Tang; Juanzhen Sun; Mu Mu (Advances in Atmospheric Sciences, 2021)

Identification and functional analysis of a pollen fertility-associated gene GhGLP4 of Gossypium hirsutum L. - Hongli Zheng; Rongjia Wang; Qimeng Jiang; Diandian Zhang; Rongrong Mu; Yihan Xu; Vitalis E. Nnaemeka; Jun Mei; Yanyan Zhao; Fangfang Cai; Dongliang Yu; Yuqiang Sun; et al. (Theoretical and Applied Genetics, 2021)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Expression and functional analysis of cytoplasmic dynein during spermatogenesis in Portunus trituberculatus - Chao-Guang Wei; Dan-Li Mu; Dao-Jun Tang; Jun-Quan Zhu; Cong-Cong Hou (Cell and Tissue Research, 2021)

A review of the ecohydrology discipline: Progress, challenges, and future directions in China - Jun Xia; Yongyong Zhang; Xingmin Mu; Qiting Zuo; Yujian Zhou; Guangju Zhao (Journal of Geographical Sciences, 2021)

Strategies for culturing active/dormant marine microbes - Da-Shuai Mu; Yang Ouyang; Guan-Jun Chen; Zong-Jun Du (Marine Life Science & Technology, 2021)

Isolation and molecular characterization of bovine herpesvirus 4 from cattle in mainland China - Jun Lin; Rui-Hong Chen; Mu-Jiao Yang; Yuan-Mao Zhu; Fei Xue (Archives of Virology, 2021)

Performance, kinetics characteristics and enhancement mechanisms in anammox process under Fe(II) enhanced conditions - Si-min Tang; Ze-hao Xu; Ya-lei Liu; Guang-feng Yang; Jun Mu; Ren-cun Jin; Qiao Yang; Xiao-ling Zhang (Biodegradation, 2020)

Analysis of melting reconstruction treatment and cement solidification on ultra-risk municipal solid waste incinerator fly ash–blast furnace slag mixtures - Zhongtao Luo; Liugang Chen; Meixiang Zhang; Lei Liu; Jun Zhao; Yuandong Mu (Environmental Science and Pollution Research, 2020)

Stem cells and vascular dementia: from basic science to the clinic - Wenxia Jiang; Lei Gong; Fang Liu; Jun Mu (Cell and Tissue Banking, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

Fine-mapping and transcriptome analysis of BoGL-3, a wax-less gene in cabbage (Brassica oleracea L. var. capitata) - Xin Dong; Jialei Ji; Limei Yang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yong Wang; Peitian Sun; Jun Tang; Dongming Liu; Yumei Liu; et al. (Molecular Genetics and Genomics, 2019)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Effect of freeze-thaw cycles on uniaxial mechanical properties of cohesive coarse-grained soils - Yong-long Qu; Guo-liang Chen; Fu-jun Niu; Wan-kui Ni; Yan-hu Mu; Jing Luo (Journal of Mountain Science, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Risk Assessment of 5-Chloro-2-Methylisothiazol-3(2H)-One/2-Methylisothiazol-3(2H)-One (CMIT/MIT) Used as a Preservative in Cosmetics - Min Kook Kim; Kyu-Bong Kim; Joo Young Lee; Seung Jun Kwack; Yong Chan Kwon; Ji Soo Kang; Hyung Sik Kim; Byung-Mu Lee (Toxicological Research, 2019)

Risk Assessment of Triclosan, a Cosmetic Preservative - Jung Dae Lee; Joo Young Lee; Seung Jun Kwack; Chan Young Shin; Hyun-Jun Jang; Hyang Yeon Kim; Min Kook Kim; Dong-Wan Seo; Byung-Mu Lee; Kyu-Bong Kim (Toxicological Research, 2019)

Risk Assessment of Ethylhexyl Dimethyl PABA in Cosmetics - Chi Rim Sung; Kyu-Bong Kim; Joo Young Lee; Byung-Mu Lee; Seung Jun Kwack (Toxicological Research, 2019)

Risk Assessment of Drometrizole, a Cosmetic Ingredient used as an Ultraviolet Light Absorber - Jae Kwon Lee; Kyu-Bong Kim; Jung Dae Lee; Chan Young Shin; Seung Jun Kwack; Byung-Mu Lee; Joo Young Lee (Toxicological Research, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Permafrost warming along the Mo’he-Jiagedaqi section of the China-Russia crude oil pipeline - Fei Wang; Guo-yu Li; Wei Ma; Yun-cheng Mao; Yan-hu Mu; Mihaela Serban; Yong-jun Cai (Journal of Mountain Science, 2019)

Permian integrative stratigraphy and timescale of China - Shuzhong Shen; Hua Zhang; Yichun Zhang; Dongxun Yuan; Bo Chen; Weihong He; Lin Mu; Wei Lin; Wenqian Wang; Jun Chen; Qiong Wu; Changqun Cao; et al. (Science China Earth Sciences, 2019)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Hoeflea prorocentri sp. nov., isolated from a culture of the marine dinoflagellate Prorocentrum mexicanum PM01 - Qiao Yang; Zhi-Wei Jiang; Cheng-Hui Huang; Ruo-Nan Zhang; Ling-Zhi Li; Guang Yang; Li-Juan Feng; Guang-Feng Yang; Heng Zhang; Xiao-Ling Zhang; Jun Mu (Antonie van Leeuwenhoek, 2018)

Drift analysis of MH370 debris in the southern Indian Ocean - Jia Gao; Lin Mu; Xianwen Bao; Jun Song; Yang Ding (Frontiers of Earth Science, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Correction to: Ponticoccus alexandrii sp. nov., a novel bacterium isolated from the marine toxigenic dinoflagellate Alexandrium minutum - Qiao Yang; Xiaoling Zhang; Lingzhi Li; Ruonan Zhang; Lijuan Feng; Jun Mu (Antonie van Leeuwenhoek, 2018)

Ponticoccus alexandrii sp. nov., a novel bacterium isolated from the marine toxigenic dinoflagellate Alexandrium minutum - Qiao Yang; Xiaoling Zhang; Lingzhi Li; Ruonan Zhang; Lijuan Feng; Jun Mu (Antonie van Leeuwenhoek, 2018)

Characterization of bacterial composition and diversity in a long-term petroleum contaminated soil and isolation of high-efficiency alkane-degrading strains using an improved medium - Jun Zheng; Jun-Qiao Feng; Lei Zhou; Serge Maurice Mbadinga; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2018)

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

Characteristics of nitrogen removal and microbial community in biofilm system via combination of pretreated lignocellulosic carriers and various conventional fillers - Jing Zhao; Lijuan Feng; Jincheng Dai; Guangfeng Yang; Jun Mu (Biodegradation, 2017)

Insertion of a solo LTR retrotransposon associates with spur mutations in ‘Red Delicious’ apple (Malus × domestica) - Mengxue Han; Qibao Sun; Junyong Zhou; Huarong Qiu; Jing Guo; Lijuan Lu; Wenlei Mu; Jun Sun (Plant Cell Reports, 2017)

An Inframe Trinucleotide Deletion in MTRR Exon 1 is Associated with the Risk of Spina Bifida - Jun Zhang; Xiao-lu Dai; Gui-cen Liu; Juan Wang; Xue-yi Ren; Mu-hua Jin; Nan-nan Mi; Shu-qin Wang (NeuroMolecular Medicine, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Optimization of continuous-flow solid-phase denitrification via coupling carriers in enhancing simultaneous removal of nitrogen and organics for agricultural runoff purification - Yi Lu; Xiaoqing Zhang; Lijuan Feng; Guangfeng Yang; Zhou Zheng; Junzhi Liu; Jun Mu (Biodegradation, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Artificial Inoculation Method of Pokkah Boeng Disease of Sugarcane and Screening of Resistant Germplasm Resources in Subtropical China - Ze-Ping Wang; Hai-Jun Sun; Qiang Guo; Shi-Qiang Xu; Ji-Hua Wang; Shan-Hai Lin; Mu-Qing Zhang (Sugar Tech, 2017)

A new quinolinone and its natural/artificial derivatives from a shark gill-derived fungus Penicillium polonicum AP2T1 - Yi Zhang; Jun Mu; Frank Essmann; Yan Feng; Markus Kramer; Hai-yan Bao; Stephanie Grond (Natural Product Research, 2017)

Interaction between southern rice black-streaked dwarf virus minor core protein P8 and a rice zinc finger transcription factor - Jing Li; Nian-Jun Cai; Jin Xue; Jian Yang; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2017)

Selenium-binding protein 1: a sensitive urinary biomarker to detect heavy metal-induced nephrotoxicity - Eui Kyung Lee; Young-Jun Shin; Eun Young Park; Nam Deuk Kim; Aree Moon; Seung Jun Kwack; Ji Yeon Son; Sam Kacew; Byung Mu Lee; Ok-Nam Bae; Hyung Sik Kim (Archives of Toxicology, 2017)

Definition of water exchange zone between the Bohai Sea and Yellow Sea and the effect of winter gale on it - Jun Song; Junru Guo; Jing Li; Lin Mu; Yulong Liu; Guosong Wang; Yan Li; Huan Li (Acta Oceanologica Sinica, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

Measurements of nitrous acid (HONO) in urban area of Shanghai, China - François Bernard; Mathieu Cazaunau; Benoît Grosselin; Bin Zhou; Jun Zheng; Peng Liang; Yujie Zhang; Xingnan Ye; Véronique Daële; Yujing Mu; Renyi Zhang; Jianmin Chen; et al. (Environmental Science and Pollution Research, 2016)

Sourcing copper ores for production of bronzes excavated at Shuangyantang, a Western Zhou (1046–771 bc) site in Chongqing (Southwest China): evidence from lead isotope analysis - Xiaopan Fan; Di Mu; Jun Yi; Hongmin Wang; Wugan Luo (Archaeological and Anthropological Sciences, 2016)

Hypermethylation of Hippocampal Synaptic Plasticity-Related genes is Involved in Neonatal Sevoflurane Exposure-Induced Cognitive Impairments in Rats - Ling-sha Ju; Min Jia; Jie Sun; Xiao-ru Sun; Hui Zhang; Mu-huo Ji; Jian-jun Yang; Zhong-yun Wang (Neurotoxicity Research, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Simulation of the extreme waves generated by typhoon Bolaven (1215) in the East China Sea and Yellow Sea - Ki Cheon Jun; Weon Mu Jeong; Jin Yong Choi; Kwang Soon Park; Kyung Tae Jung; Mee Kyung Kim; Jang Won Chae; Fangli Qiao (Acta Oceanologica Sinica, 2015)

The radiologic technologists’ health study in South Korea: study design and baseline results - Won Jin Lee; Mina Ha; Seung-sik Hwang; Kyoung-Mu Lee; Young-Woo Jin; Meeseon Jeong; Jae Kwan Jun; Eun Shil Cha; Yousun Ko; Kyung-Hwa Choi; Jung-Eun Lee (International Archives of Occupational and Environmental Health, 2015)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

Analysis of small RNAs derived from Chinese wheat mosaic virus - Jian Yang; Shi-Ling Zheng; Heng-Mu Zhang; Xiao-Ya Liu; Jing Li; Jun-Min Li; Jian-Ping Chen (Archives of Virology, 2014)

Four chlorinated depsidones from a seaweed-derived strain of Aspergillus unguis and their new biological activities - Yi Zhang; Jun Mu; Yan Feng; Lixue Wen; Jinyuan Han (Natural Product Research, 2014)

Resveratrol Pretreatment Attenuates the Isoflurane-Induced Cognitive Impairment Through its Anti-Inflammation and -Apoptosis Actions in Aged Mice - Xiao-min Li; Mai-tao Zhou; Xing-ming Wang; Mu-huo Ji; Zhi-qiang Zhou; Jian-jun Yang (Journal of Molecular Neuroscience, 2014)

Clinical and laboratory characteristics of patients having amyloidogenic transthyretin deposition in osteoarthritic knee joints - Ya-Jun Gu; Peng Ge; Yun Mu; Jin-Hai Lu; Fang Zheng; Xu-Guo Sun (Journal of Zhejiang University-SCIENCE B, 2014)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Genetic diversity of two Tibetan macaque (Macaca thibetana) populations from Guizhou and Yunnan in China based on mitochondrial DNA D-loop sequences - Li-Jing Zhong; Ming-Wang Zhang; Yong-Fang Yao; Qing-Yong Ni; Jun Mu; Chong-Qing Li; Huai-Liang Xu (Genes & Genomics, 2013)

HBV infection increases the risk of pancreatic cancer: a meta-analysis - Gang Luo; Ning-Bo Hao; Chang-Jiang Hu; Xin Yong; Mu-Han Lü; Bo-Jun Cheng; Yao Zhang; Shi-Ming Yang (Cancer Causes & Control, 2013)

Environmental capacity of petroleum hydrocarbon pollutants in Jiaozhou Bay, China: Modeling and calculation - Keqiang Li; Ying Su; Jun Ying; Xiulin Wang; Jinbo Mu (Journal of Ocean University of China, 2013)

Isolation and functional analysis of Thmfs1, the first major facilitator superfamily transporter from the biocontrol fungus Trichoderma harzianum - Mu Liu; Jun Liu; Wei Min Wang (Biotechnology Letters, 2012)

Rosiglitazone inhibits angiotensin II-induced C-reactive protein production in human aortic endothelial cells through regulating AT1–ROS–MAPK signal pathway - Chun-Jie Han; Jun-Tian Liu; Ming Li; Mu Cui; Xiao-Ming Pang; Jun-Jun Mao; Xiao-Fang Liu (Inflammation Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Participatory agroforestry development for restoring degraded sloping land in DPR Korea - Jianchu Xu; Meine van Noordwijk; Jun He; Kwang-Ju Kim; Ryong-Song Jo; Kon-Gyu Pak; Un-Hui Kye; Jong-Sik Kim; Kwon-Mu Kim; Yong-Nam Sim; Je-Un Pak; Ki-Ung Song; et al. (Agroforestry Systems, 2012)

De novo characterization of the root transcriptome of a traditional Chinese medicinal plant Polygonum cuspidatum - DaCheng Hao; Pei Ma; Jun Mu; ShiLin Chen; PeiGen Xiao; Yong Peng; Li Huo; LiJia Xu; Chao Sun (Science China Life Sciences, 2012)

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Low-frequency variability of a semi-closed sea induced by the circulation in an adjacent ocean in a wind-driven, quasi-geostrophic, eddy-resolving simulation - Lin Mu; Linhao Zhong; Lijuan Hua; Jun Song (Ocean Dynamics, 2011)

Numerical study of M2 internal tide generation and propagation in the Luzon Strait - Huan Li; Dan Song; Xueen Chen; Hongbao Qian; Lin Mu; Jun Song (Acta Oceanologica Sinica, 2011)

Vertical structure and seasonal variation of tidal and residual currents in the northern Huanghai Sea - Jun Song; Junru Guo; Lulu Qiao; Lin Mu; Zhigang Yao; Yang Liu; Huan Li; Xianwen Bao; Xiaoyan Sun; Jia Gao (Acta Oceanologica Sinica, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Characterization of peptidoglycan hydrolase in Cag pathogenicity island of Helicobacter pylori - Qiao Zhong; Shihe Shao; Runhong Mu; Hua Wang; Shiteng Huang; Jun Han; He Huang; Shuwei Tian (Molecular Biology Reports, 2011)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Physicochemical evolution and positive selection of the gymnosperm matK proteins - Da Cheng Hao; Jun Mu; Shi Lin Chen; Pei Gen Xiao (Journal of Genetics, 2010)

Molecular phylogeny, long-term evolution, and functional divergence of flavin-containing monooxygenases - Da Cheng Hao; Shi Lin Chen; Jun Mu; Pei Gen Xiao (Genetica, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Sulfotransferase 1A1 and glutathione S-transferase P1 genetic polymorphisms modulate the levels of urinary 8-hydroxy-2′-deoxyguanosine in betel quid chewers - Ruey-Hong Wong; Chiung-Wen Hu; Ching-Ying Yeh; Mu-Rong Chao; Chin-Chun Chen; Jun-Huang Huang; Shih-Hsien Chang; Shin-I Lee; Hong-Shen Lee (Archives of Toxicology, 2008)

Efficient organogenesis and plantlet regeneration in the timber species Cunninghamia lanceolata (Lamb.) Hook - Mu-lan Zhu; Ji Wang; Yang Yu; Sheng-jun Liu; Zhi-ming Wei (In Vitro Cellular & Developmental Biology - Plant, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Microbial production of 1,3-propanediol from glycerol by Klebsiella pneumoniae under micro-aerobic conditions up to a pilot scale - Hai-Jun Liu; Dai-Jia Zhang; You-Hai Xu; Ying Mu; Ya-Qin Sun; Zhi-Long Xiu (Biotechnology Letters, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Expression and immunogenicity of an Escherichia coli K99 fimbriae subunit antigen in soybean - Kenneth J. Piller; Thomas E. Clemente; Sang Mu Jun; Cynthia C. Petty; Shirley Sato; David W. Pascual; Kenneth L. Bost (Planta, 2005)